Experimental Infection of Mosquitoes with Dirofilaria repens (Nematoda, Filarioidea) Larvae - Kuzmin, Yu.; Varodi, E.; Vasylyk, N.; Kononko, G. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2005)
Gravid females of three mosquito species: Anopheles maculipennis atroparvus, Culex pipiens molestus and Aedes aegypti, all from laboratory cultures, were experimentally infected with microfilaria of Dirofilaria repens from blood of a domestic dog from vicinity of Kyiv (Ukraine). Larval stages of the nematode successfully developed in all three vector species at room temperature 18–29°C. Microfilaria migrated from the stomach and intestine to the Malpighian tubules of mosquitoes during first three days post infection (pi). Quiescent first-stage larvae ("sausage stage") were first observed on day 4 pi; in some specimens of Ae. aegypti this stage remained in Malpighian tubules till day 21 pi (end of observations). Second stage larvae were observed from day 6 till day 19 pi. Third stage larvae were first observed in Malpighian tubules of all three mosquito species on day 10 pi; on days 14 and 16 pi they were first found in body cavity, salivary glands and proboscis. The following values of vector efficiency index were calculated for each mosquito species: 11.9% in A. maculipennis, 7.9% in Ae. aegypti and 1.9% in C. pipiens. General morphology of experimentally obtained D. repens larval stages is described. A. maculipennis atroparvus and C. pipiens molestus are supposed to participate in the D. repens transmission under natural conditions in Ukraine. Гоноактивные самки комаров Anopheles maculipennis atroparvus, Culex pipiens molestus и Aedes aegypti из лабораторных культур были экспериментально заражены микрофиляриями Dirofilaria repens из крови собаки из окр. Киева (Украина). Во всех трех видах переносчиков происходило развитие личиночных стадий нематоды при комнатной температуре 18–29°C. Микрофилярии мигрировали из желудка и кишечника в мальпигиевы сосуды комаров в первые трое суток после заражения. Покоящиеся личинки первой стадии наблюдались в мальпигиевых сосудах начиная с 4-х сут эксперимента; в некоторых особях Ae. aegypti эти личинки оставались до 21-х сут эксперимента (окончание наблюдений). Личинки второй стадии обнаруживались с 6-х по 19-е сут. Первые личинки третьей стадии наблюдались в мальпигиевых сосудах на 10-е сут; на 14-е и 16-е сут они проникали в полость тела, слюнные железы и хоботок комаров. Индекс эффективности переносчиков был равен 11,9% у A. maculipennis, 7,9% у Ae. aegypti и 1,9% у C. pipiens. Даны описания личиночных стадий D. repens из промежуточных хозяев. Предполагается, что A. maculipennis atroparvusi и C. pipiens molestus участвуют в циркуляции D. repens в естественных условиях в Украине.